The effect of technology utilization and creativity in the digital era on teacher performance: Inggris - Adawiyah, Robiatin; Waringin, Iftitah Allaun; Putri, Nabilla Noviana; Sudrajat, Tyara Nur Chomala; Hariz, Hariz; Sekarini, Ratih Ayu (Institute of Computer Science (IOCS), 2025)
Technology ultilizing and teacher creativity in the digital era are userful for developing teacher performance in learning methods, teacher activities in technology utilization and teacher creativity in the digital era affect teacher performance to create learning that is not monotonous. This analysis is carrired out to find solution to problems regarding technology utilization. At SD.MI Jauharatun Naqiyah facilitates the lab to its students to be used as learning materials, the teacher uses Youtube, Zoom, and applications for learning so that studen are more interested in learning. Then ice Breaking is done to warm up before te satart of learning, the teacher also have E-Learning which is used for student assessment, as a result of this application, student are more somfortable in learning, if they do not feel bored quikly with the classromm learning atmosphere, of course, it also guides student to get used to digital technology, what is in SD/MI Jauharatun Naqiyah uses applications during the learning process, not only through Google Form, SD/MI Jauharatun Naqiyah also uses applications in making question and materials to its students.